ETHNIC SPIRIT OF THRIPILLYA AND IT’S PLACE IN CULTURAL GENESIS - Петруня-Пилявська, Н. А (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with process of establishing and development of ethnic spirit of Thripillya, its forms of art and involutive transformations in Ukrainian cultural genesis.